Navigating academic expectations and social integration: a moderated mediation analysis of cultural adaptation, peer support, and well-being among Chinese international students - Xu, Jincheng; Chai, Wenyu (Frontiers in Psychology, 2025)
International students often encounter significant academic and cultural challenges that can adversely affect their psychological well-being. This study examines the association between academic expectations and well-being of Chinese international students, with cultural adaptation and social integration modeled as parallel mediators, and peer support as a moderator. A cross-sectional survey was conducted among 456 Chinese international students enrolled in universities. The findings reveal that academic expectations have a direct negative effect on student well-being and also exert significant indirect effects through both cultural adaptation and social integration. Moreover, peer support moderates the negative relationship between academic expectations and both mediators, thereby reducing their adverse association with well-being. The moderated mediation analysis confirms that high levels of peer support buffer the detrimental effects of academic pressure by enhancing students’ adaptive and integrative capacities. These results underline the importance of fostering peer-based support systems and culturally responsive interventions in promoting international student well-being. The study contributes to the growing body of research on acculturative stress and offers practical implications for student affairs professionals and institutional policymakers.